2008
DOI: 10.1111/j.1365-2125.2007.03081.x
|View full text |Cite
|
Sign up to set email alerts
|

Systemic and bronchodilator effects of inhaled rac‐formoterol in subjects with chronic obstructive pulmonary disease: a dose–response study

Abstract: WHAT IS ALREADY KNOWN ABOUT THIS SUBJECT• The long-acting inhaled b2-agonist formoterol has systemic effects when taken in high doses.• It can be used as relief medication in asthma and there is interest in this approach in chronic obstructive pulmonary disease (COPD).• Relief medication can involve high doses, and in subjects with COPD who have limited ability to bronchodilate the adverse effects can outweigh the benefits.• There are concerns with the overall safety of high-dose b2-agonists in subjects with C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Conventional dose-ranging trials for bronchodilators, such as those used to evaluate tiotropium, salmeterol and formoterol [ 8 , 10 - 12 , 20 ], rely on hypothesis testing and use of contrast statistics and do not provide a rigorous basis for identification of the minimally effective, optimal or maximum doses. This is due to the low signal-to-noise ratio inherent in the measurement of FEV 1 and the poor precision of the conventional methodologies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Conventional dose-ranging trials for bronchodilators, such as those used to evaluate tiotropium, salmeterol and formoterol [ 8 , 10 - 12 , 20 ], rely on hypothesis testing and use of contrast statistics and do not provide a rigorous basis for identification of the minimally effective, optimal or maximum doses. This is due to the low signal-to-noise ratio inherent in the measurement of FEV 1 and the poor precision of the conventional methodologies.…”
Section: Discussionmentioning
confidence: 99%
“…trough FEV 1 for evaluation of bronchodilators in COPD), a dose response is established and a target dose can be selected as the smallest dose that differs from placebo and has both a clinically relevant effect and an acceptable safety profile [ 7 ]. Several such studies have evaluated dose responses for bronchodilators in patients with COPD [ 8 - 12 ]. In Phase II dose-ranging studies in COPD, indacaterol consistently demonstrated bronchodilator efficacy that was superior to placebo, regardless of the dose tested [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…The maximum effect achieved soon after dosing, otherwise known as the ‘peak’ effect, is also of interest for efficacy and safety reasons. A very high peak effect may indicate high levels of acute drug exposure that could predispose patients to β-agonist-mediated side effects, such as cardiovascular adverse events, when receiving chronic treatment [ 17 ]. Moreover, the ideal pharmacologic characteristic of a once-daily LABA is a low ‘peak to trough ratio’, ensuring relatively stable lung function throughout the day [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown the efficacy of formoterol in acute non-severe asthma, acute severe asthma, exercise induced bronchospasm, childhood asthma, and COPD. [15][16][17][18][19] Although few studies have shown clinically significant improvement in lung function (FEV1) with formoterol when compared with salbutamol, 16 most studies have shown a comparable efficacy. 15,17 Safety of formoterol is also well documented even at high doses in patients with asthma and COPD.…”
Section: Discussionmentioning
confidence: 99%